Pink-beam serial crystallography - A. Meents (Nature Portfolio, 2017)
Serial X-ray crystallography (SX) is used for data collection at X-ray Free Electron Lasers. Here the authors show that a polychromatic “pink” synchrotron X-ray beam can be used for SX, which is useful when crystal supply is limited and will allow time-resolved measurements at synchrotron sources in the future.